Students' Perception of Kitchen Activity Groups in Promoting Understanding of Thermodynamics Concepts and Problem-Solving Skills in Secondary School Chemistry - Ngozi, Okafor (NIU Journal of Humanities, 2021)
This study investigated students' perception of kitchen activity groups in promoting understanding of thermodynamics concepts and problem solving skills in chemistry. Four null hypotheses guided the study. It was quantitative survey and correlational research designs which involved 250 coeducational public Senior Secondary School 3 (SSS 3) chemistry students in Lagos State of Nigeria. Three instruments were used in data collection and data were analyzed using mean, standard deviation, Pearson correlation coefficient, MANOVA and ANOVA. Results show that students perceived Energy Transfer (ET) and Thermodynamics Meaning (TM) as kitchen activity groups that promoted students Understanding of Thermodynamics Concepts (UTC) and Problem-Solving Skills (PSS) respectively. Gender was also perceived to significantly contribute in promoting students' UTC and PSS in chemistry respectively in favour of male students. The results also show significant combined contributions of kitchen activity groups, gender and age groups in promoting students' understanding of thermodynamics concepts and problem-solving skills in chemistry. The paper concludes that to be successful in post-primary environment, school leavers should embrace learning of chemistry at home that is fun and inspiring in solving learning difficulties of the 21st century education and suggests that since good education and skills acquisition begin at home, therefore, secondary school chemistry teachers should liaise with parents or guardians to synergize difficulties students encounter in learning chemistry concepts by relating them to home chores around the kitchen. Keywords: Gender, Age, Kitchen Activities, Thermodynamics